Comparative Proteomics of Tandem Mass Spectrometry Analyses for Bacterial Strains Identification and Differentiation - Jabbour, Rabih E.; Wade, Mary M.; Deshpande, Samir V.; Stanford, Michael F.; Zulich, Alan W.; Snyder, A. Peter (IntechOpen, 2012)
None